Abnormal uterine bleeding: management algorithms, treatment approaches - Yu.E. Dobrokhotova; Saprykina L.V.; Filatova L. A.; M.R. Narimanova (РМЖ. Мать и дитя, 2020)
Yu.E. Dobrokhotova, L.V. Saprykina, L.A. Filatova, M.R. Narimanova Pirogov Russian National Research Medical University, Moscow, Russian Federation Abnormal uterine bleeding (AUB) is a common disorder which describes irregularities in the menstrual cycle involving frequency, regularity, duration, and volume of flow in non-pregnant women. AUB has a significant impact on physical, psychological, social, and professional aspects and family life. Currently, both medications and surgical procedures are used for AUB treatment. Medical treatment involves non-hormonal and hormone therapy. Drug choice is determined by symptom severity, reproductive life plan etc. Hormone therapy includes combined hormonal contraceptives, progestogens (including levonorgestrel-releasing intrauterine system), agonists and antagonists of gonadotropin-releasing hormone. Non-hormonal treatment includes nonsteroidal anti-inflammatory drugs (NSAIDs), tranexamic acid (TXA), and other hemostatic agents. TXA provides antifibrinolytic effect and significantly reduces blood loss in women with AUB from the first days of the treatment. The recom mended dosage of TXA is 1,000 mg per os thrice daily until menorrhagia control. This dosage can be increased to 4,000 mg daily in massive bleeding. Population studies did not find any relationship between TXA and increased risk of venous thromboembolism. Keywords: abnormal uterine bleeding, combined hormonal contraceptives, progestogens, levonorgestrel-releasing intrauterine system, gonadotropin-releasing hormone agonists, nonsteroidal anti-inflammatory drugs, tranexamic acid, hormone therapy, non-hormonal treatment. For citation: Dobrokhotova Yu.E., Saprykina L.V., Filatova L.A., Narimanova M.R. Abnormal uterine bleeding: management algorithms, treatment approaches. Russian Journal of Woman and Child Health. 2020;3(1):55–60. DOI: 10.32364/2618-8430-2020-3-1-55-60.